CFD based prediction of erosion rate in large scale wall-fired boiler - Gandhi, Mikilkumar; Vuthaluru, Rupa; Vuthaluru, Hari; French, D.; Shah, K. (Elsevier, 2012)
In pulverised coal fired boilers, entrained fly ash particles in the flue gas may cause erosive wear on metal surfaces along the flow field. This can have a significant effect on the operational life of various sections of the boiler (in particular convective heat exchanger tubes). In this work, Computational Fluid Dynamics (CFD) based code FLUENT was used in conjunction with a developed erosion model for a large-scale furnace to understand the flow field and identify the areas likely to be subjected to erosion under various operating conditions. An Eulerian–Lagrangian approach was used to analyse the continuum phase and particle tracking for individual coal particles. The flow field has been thoroughly examined in terms of velocity, particle and temperature profiles along the gas flow path. The data obtained on particle velocities and trajectories have been utilised to predict the extent of erosion in selected areas of the boiler. Predictions have been found to be in good agreement with the published data as well as plant observations for velocities ranging from 15 to 32 m/s showing a deviation of 0.60%. The results obtained from the present work for understanding erosion pattern in boilers are not only of practical significance but also provide a platform for the development of an erosion tool which could assist power utilities in avoiding unnecessary shutdowns and penalties associated with replacement of boiler components.